CHARACTER BUILDING DAN PENGEMBANGAN EKOWISATA PEKON PAKU KABUPATEN TANGGAMUS PROVINSI LAMPUNG MELALUI PRINSIP PIIL PENSENGGIRI - Sosmiarti Sosmiarti; Syamsuardi Syamsuardi; Muhammad Ismail Syahputra (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2018)
Pekon paku is one of the isolated villages in Kelumbayan District, Tanggamus District, Lampung Province. Various tourism potentials and natural resources have not been well managed by the government and local communities. Therefore, the National Community Service of the 2018 KKN-Western State University BKS activities are carried out through various creative work programs. This activity is carried out by a causal method, which is to carry out a work program based on SWOT analysis of problems that occurs as a prosperous population of less than 15%, primary school conditions that are prioritized, and so on. The results of this activity are found in physical and non-physical forms. Physically, KKN students succeeded in making small platforms / shelters on the bay of the bay, holding reading gardens for elementary students, and smart mushalla. Non-physical, character building is carried out through tutoring, afternoon movements of recitation, and non-physical development of tourism in the form of promotions and beach nail bays tour shortcuts by creating a paradiseofpaku.com website. through KKN activities conducted for 30 days, students have succeeded in contributing to the pakon as a form of community service.